New records of caridean shrimp (Crustacea: Decapoda) from hydrothermally influenced fields off Futuna Island, Southwest Pacific, with description of a new species assigned to the genus Alvinocaridinides Komai & Chan, 2010 (Alvinocarididae) - Komai, Tomoyuki; Menot, Lenaick; Segonzac, Michel (Zootaxa, 2016)
Five species of caridean shrimp, including four Alvinocarididae Christoffersen, 1986 and one thorid species of the genus Lebbeus White, 1847, are reported from the recently discovered hydrothermal vent field off Futuna Island in the Southwest Pacific (depths 1418–1478 m): Alvinocaridinides semidentatus n. sp., Alvinocaris komaii Zelnio & Hourdez, 2009, Nautilocaris saintlaurentae Komai & Segonzac, 2004, Rimicaris variabilis (Komai & Tsuchida, 2015), and Lebbeus wera Ahyong, 2009. The new species, provisionally assigned to Alvinocaridinides Komai & Chan, 2010, is readily distinguished from the type species of the genus, A. formosa Komai & Chan, 2010, by the characteristic armature of the rostrum and of the propodi of the third and fourth pereopods and the possession of ischial spines on the third and fourth pereopods. Identification of R. variabilis has been confirmed by morphology and sequence comparison of mitochondrial COI gene. The geographical range of L. wera is extended to the north from the Brothers Caldera in the Kermadec Ridge.